2006
DOI: 10.2214/ajr.05.1394
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Angiography After Vascular Perfusion with Diesel Oil and a Lipophilic Contrast Agent

Abstract: After establishing a postmortem circulation by diesel oil perfusion, angiography can be performed by injection of Lipiodol Ultra Fluide. The resolution of the images obtained up to 3 days after death is comparable to that achieved in clinical angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
1
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 15 publications
1
86
1
4
Order By: Relevance
“…A recently developed pressure-controlled perfusion device (Virtangio Ò , Fumedica AG, Maquet Ò , Muri, Switzerland) was used to inject a mixture of contrast agent (Angiofil Ò , Fumedica AG, Muri, Switzerland) and paraffin oil (liquid paraffin obtained from the local pharmacy) according to the protocol proposed by Grabherr et al [16]. This oily contrast has an appropriated viscosity for the perfusion of human bodies [19], allowing for optimal perfusion conditions for high-resolution The radiological interpretations of all images were performed by both a board certified radiologist specialized in vascular radiology and a board certified forensic pathologist trained in forensic imaging. They were both blinded to the autopsy results.…”
Section: Radiological Examination and Interpretationmentioning
confidence: 99%
“…A recently developed pressure-controlled perfusion device (Virtangio Ò , Fumedica AG, Maquet Ò , Muri, Switzerland) was used to inject a mixture of contrast agent (Angiofil Ò , Fumedica AG, Muri, Switzerland) and paraffin oil (liquid paraffin obtained from the local pharmacy) according to the protocol proposed by Grabherr et al [16]. This oily contrast has an appropriated viscosity for the perfusion of human bodies [19], allowing for optimal perfusion conditions for high-resolution The radiological interpretations of all images were performed by both a board certified radiologist specialized in vascular radiology and a board certified forensic pathologist trained in forensic imaging. They were both blinded to the autopsy results.…”
Section: Radiological Examination and Interpretationmentioning
confidence: 99%
“…30 A first feasibility study, performed on an animal model, showed the success of the concept in using diesel oil as a perfusate and a roller pump as a perfusion device. 31 Multiple imaging at defined intervals permitted a dynamic visualization of the arterial, parenchymal and venous systems. This technique was later on adapted on a human model by changing the perfusion liquid and the injection technique.…”
Section: Post-mortem Angiography Goes Forensic Imaging-introduction Omentioning
confidence: 99%
“…It is yellowish, nearly odourless and stable under normal conditions (room temperature). The advantages of using oily liquids for the injection into vessels are well known and have been described in a previous article [40] that stated that combining an oily perfusate with a lipophilic contrast agent allows postmortem circulation to be established and the performance of subsequent high-resolution angiography to be carried out. Microscopic studies reported in the same article revealed that the oil may block the capillary region due to fatty embolism, which is especially vulnerable to postmortem permeability.…”
Section: Discussionmentioning
confidence: 99%
“…In order to perfuse a human body, paraffinum liquidum has proven to be the most appropriate [2]. The use of the more viscous paraffinum perliquidum however, may lead to significant extravasations, especially in regions with high autolytic activities such as the pancreas and gastric mucosa [40,42]. By diluting Angiofil Ò with a solvent such as decane, its viscosity can be decreased so as to enter the capillar-ies and become a contrast agent used in microangiography [43].By using Angiofil Ò together with paraffinum liquidum as solvent, as proposed according to the standardized protocol of PMCTA, the kinematic viscosity of the mixture is around 67-74 mm 2 /s (measured at 40 °C).…”
Section: Discussionmentioning
confidence: 99%